Posisi Kerja Dengan Keluhan Nyeri Punggung Bawah Pada Penjahit Pakaian - Kamariah Kamariah; Arifin Arifin; Gunung Setiadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
Low back pain is one of the musculoskeletal disorders resulting from the wrong ergonomics. Such conditions can occur in the informal work sector, such as clothes tailors at the Martapura Bauntung Batuah Market. The purpose of this study was to determine the relationship of work position with complaints of lower back pain in clothes tailors at the Bauntung Batuah Market Martapura. This study is an analytical study with a cross-sectional approach. The sampling technique uses total sampling with criteria for male sex so that the number of samples is 43 people. Data will be analyzed using the x2 test (Chi-square). The results of the statistical analysis obtained the value of the work position p-value of 0,000 meaning that there is a relationship between the work position and complaints of lower back pain in the clothes tailor at the Martapura Bauntung Batuah Market. For other researchers, further research needs to being done on other factors such as individual factors and physical environmental factors that can cause complaints of lower back pain.